Development of iminosugar-based glycosidase inhibitors as drug candidates for SARS-CoV-2 virus via molecular modelling and in vitro studies - Zorana Ferjancic; Filip Bihelovic; Bojan Vulovic; Radomir Matovic; Milena Trmcic; Aleksandar Jankovic; Milos Pavlovic; Filip Djurkovic; Radivoje Prodanovic; Aleksandra Djurdjevic Djelmas; Nevena Kalicanin; Mario Zlatovic; et al. (Journal of Enzyme Inhibition and Medicinal Chemistry)
We developed new iminosugar-based glycosidase inhibitors against SARS-CoV-2. Known drugs (miglustat, migalastat, miglitol, and swainsonine) were chosen as lead compounds to develop three classes of glycosidase inhibitors (α-glucosidase, α-galactosidase, and mannosidase). Molecular modelling of the lead compounds, synthesis of the compounds with the highest docking scores, enzyme inhibition tests, and in vitro antiviral assays afforded rationally designed inhibitors. Two highly active α-glucosidase inhibitors were discovered, where one of them is the most potent iminosugar-based anti-SARS-CoV-2 agent to date (EC90 = 1.94 µM in A549-ACE2 cells against Omicron BA.1 strain). However, galactosidase inhibitors did not exhibit antiviral activity, whereas mannosidase inhibitors were both active and cytotoxic. As our iminosugar-based drug candidates act by a host-directed mechanism, they should be more resilient to drug resistance. Moreover, this strategy could be extended to identify potential drug candidates for other viral infections.